Bentuk Penyajian Tari Lemea Di Sanggar Dulang Mas Pada Acara AMAN Di Desa Lubuk Kembang - Auliannisa Ramadhani; Herlinda Mansyur (Jurnal Kajian dan Penelitian Umum, 2023)
This study aims to describe the form of presentation of the Lemea Dance at the Dulang Mas Studio at the Alliance of Indigenous Peoples of the Archipelago in Lubuk Kembang Village, North Curup District, Rejang Lebong Regency. This type of research is qualitative using descriptive analysis method. The key research instruments were the researchers themselves and assisted by data collection equipment such as stationery, interview guides, photo cameras and video cameras. The data in this study uses primary data and secondary data. Data collection techniques were carried out by means of literature study, observation, interviews and documentation. The steps to analyze the data are data reduction, data presentation and data verification. The results showed that the form of presentation of the Lemea dance at Dulang Mas Studio at the Archipelago Indigenous Peoples Alliance event at Lubuk Kembang Village, North Curup District, Rejang Lebong Regency was a creative dance with a representational form of presentation and functioned as entertainment. The elements in the presentation of the Lemea Dance consist of 5 dance movements, 6 female dancers, musical accompaniment (Accordion, Gong, Tamtam, Redap, Kulintang, Tamborin, Toktok and Cymbals), clothing styles (belts, outerwear and cloth belts) and the addition of head accessories (buns, orange flowers, cempako flowers, and yellow scarves tied in a bun) and other accessories (bracelets, coin necklaces and earrings), make-up using beautiful makeup, props (Sauk, Kerontong, Taleng Cakik , Dapar, Knife and Gerigik), and the performance venue for this Lemea Dance is displayed in an open field in front of the main stage.